Spinal cord stimulation is safe and feasible in patients with advanced heart failure: early clinical experience. (24th June 2014) - Torre‐Amione, Guillermo; Alo, Kenneth; Estep, Jerry D.; Valderrabano, Miguel; Khalil, Nashwa; Farazi, Taraneh G.; Rosenberg, Stuart P.; Ness, Lanitia; Gill, John
Abstract Aims Pre‐clinical work suggests that upper thoracic spinal cord stimulation (SCS) may have therapeutic effects in the treatment of heart failure (HF). We therefore aim to assess the safety and feasibility of SCS in HF patients. Methods and results A prospective, randomized, double‐blind, crossover pilot study was conducted in symptomatic HF patients receiving optimal medical therapy. Patients were implanted with an SCS system and randomized to an SCS‐ACTIVE, delivered at 90% paraesthesia threshold, or an SCS‐INACTIVE phase for 3 months, followed by a 1‐month washout period and crossover to the alternative phase. The safety of SCS therapy was assessed by death and cardiac events. Implantable cardioverter defibrillator (ICD) function in the presence of SCS was tested by defibrillation testing during SCS system implant and review of real‐time and stored electrograms during follow‐up. The efficacy of SCS therapy was assessed by changes in patient symptoms, LV function, and BNP level. Nine patients were investigated. In all cases, ICD sensing, detection, and therapy delivery were unaffected by SCS. During follow‐up, one patient died and one was hospitalized for HF while in the SCS‐INACTIVE phase, and two patients had HF hospitalizations during the SCS‐ACTIVE phase. Symptoms were improved in the majority of patients with SCS, while markers of cardiac structure and function were, in aggregate, unchanged. Conclusion This study shows that an SCS system can be safely implanted in patients with advanced HF and that the SCS system does not interfere with ICD function.